1996
DOI: 10.1007/bf02786962
|View full text |Cite
|
Sign up to set email alerts
|

Milk-clotting activity of cucumisin, a plant serine protease from melon fruit

Abstract: Cucumisin (EC 3.4.21.25) isolated from prince melon fruit is a plant serine protease. Its milk-clotting activity was compared with plant cysteine proteases such as papain (EC 3.4.22.2) and ficain (EC 3.4.22.3). Cucumisin was more stable than papain under the condition of pH 7.1, 37 degrees C for 24 h. The milk-clotting activity of cucumisin was the same to that of papain and was half value of that of ficain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A serine protease of Cucumis melo fruit exhibited a more stable milk-clotting activity, when compared to that of papain (Uchikoba & Kaneda, 1996). Additionally, it has been reported that a serine protease from Lactuca sativa leaves promoted clotting of skim milk as well as of milk with different fat contents (Lo Piero et al, 2002;Uchikoba & Kaneda, 1996). Aspartic protease from Oryza sativa seeds promoted cleavage of j-casein, in a pattern similar to that obtained with chymosin and pepsin (Asakura, Watanabe, Abe, & Arai, 1997), and aspartic proteases from extract of Silybum marianum flowers hydrolysed caprine and ovine milk caseins (Cavalli, Silva, Cimino, Malcata, & Priolo, 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A serine protease of Cucumis melo fruit exhibited a more stable milk-clotting activity, when compared to that of papain (Uchikoba & Kaneda, 1996). Additionally, it has been reported that a serine protease from Lactuca sativa leaves promoted clotting of skim milk as well as of milk with different fat contents (Lo Piero et al, 2002;Uchikoba & Kaneda, 1996). Aspartic protease from Oryza sativa seeds promoted cleavage of j-casein, in a pattern similar to that obtained with chymosin and pepsin (Asakura, Watanabe, Abe, & Arai, 1997), and aspartic proteases from extract of Silybum marianum flowers hydrolysed caprine and ovine milk caseins (Cavalli, Silva, Cimino, Malcata, & Priolo, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…A serine protease of Cucumis melo fruit exhibited a more stable milk-clotting activity, when compared to that of papain (Uchikoba & Kaneda, 1996). Additionally, it has been reported that a serine protease from Lactuca sativa leaves promoted clotting of skim milk as well as of milk with different fat contents (Lo Piero et al, 2002;Uchikoba & Kaneda, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Cucumisin exhibited the same milk-clotting activity of CPs such as papain, but in addition, it produced much less bitter-tasting peptides than those formed by more typical plant CPs (Uchikoba and Kaneda 1996). Other SP enzyme, Lettucine (not included in IUBMB), from L. sativa leaves, is able to provoke a significant disorganization of the micellar structure of casein.…”
Section: Dairy Industrymentioning
confidence: 97%
“…Pardo et al (2010), using casein as substrate, found that extracts form Asclepias fruticosa seeds exhibited a lower MCA/PA ratio (0.68) than the value reported in this study. In addition, proteases found in Jacaratia curumbensis (Arruda et al 2012), Lactuca sativa (Lo Piero et al 2002) and Asclepias fruticosa (Trejo et al 2001) and Onopordon acanthium (Brutti et al 2012), Cucumis melo (Uchikoba and Kaneda, 1996) and Zingiber officinale cv. Laiwu Shandong (Hashim et al 2011) possessed high caseinolytic activity in comparison with calf chymosin limiting their application for cheesemaking.…”
Section: Proteolytic Activity In B Pinguin Fruit Extractmentioning
confidence: 99%